Addressing violence against transgender people in Bangladesh: A call for policy intervention - Barua, Arup; Khan, Shehreen Ataur (Frontiers in Sociology, 2023)
The history of violence, oppression and cruelty is as old as human civilization. Human identity has multiple layers, and divergence from a particular identity may invoke violence, deprivation and discrimination in disparate contexts. Transgender community is one of the vulnerable groups in many societies and countries for their gender incongruence. Conventional customs and people’s social unconsciousness transmit intergenerational violence against transgender people – which repress and alienate them from enjoying their fundamental human rights. The key objectives of this paper are twofold. First, this paper focuses on violence against transgender community and violation of their rights in Bangladesh. Second, it analyzes categories of violence against transgender as well stakeholders to be involved in addressing a solution. In addition, this paper sheds light on the recent institutional developments in promoting welfare and rights of the transgender population in Bangladesh. Finally, this article contends that absence of a devoted national policy for the protection and welfare of the transgender population creates an impasse to undertake required course of actions – which should be thrived with appropriate policy formulation and effective implementation.